Computational Physics Simulation of Classical and Quantum Systems - Scherer, Philipp O. J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book encapsulates the coverage for a two-semester course in computational physics. The first part introduces the basic numerical methods while omitting mathematical proofs but demonstrating the algorithms by way of numerous computer experiments. The second part specializes in simulation of classical and quantum systems with instructive examples spanning many fields in physics, from a classical rotor to a quantum bit. All program examples are realized as Java applets ready to run in your browser and do not require any programming skills.
Numerical Methods -- Error Analysis -- Interpolation -- Numerical Differentiation -- Numerical Integration -- Systems of Inhomogeneous Linear Equations -- Roots and Extremal Points -- Fourier Transformation -- Random Numbers and Monte Carlo Methods -- Eigenvalue Problems -- Data Fitting -- Equations of Motion -- Simulation of Classical and Quantum Systems -- Rotational Motion -- Simulation of Thermodynamic Systems -- Random Walk and Brownian Motion -- Electrostatics -- Waves -- Diffusion -- Nonlinear Systems -- Simple Quantum Systems.
Keywords: Physics; Chemistry, Physical organic; Chemistry; Computer science -- Mathematics; Physics; Numerical and Computational Physics; Statistical Physics, Dynamical Systems and Complexity; Theoretical and Computational Chemistry; Computational Mathematics and Numerical Analysis; Physical Chemistry